2022
DOI: 10.1002/pbc.29962
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus vaccination uptake among childhood cancer survivors in Western New York

Abstract: Introduction The risk of human papillomavirus (HPV)‐associated cancers is significantly higher among survivors of a childhood cancer compared to the general population. Despite this, their HPV vaccine uptake rates are lower. We examined factors related to HPV vaccine uptake among childhood cancer survivors from Western New York over 13 years following the introduction of HPV vaccines. Methods Retrospective review of patients diagnosed with invasive or noninvasive cancerous conditions at age 9 or younger treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Vaccination is imperative for preventing HPV-related disease because, aside from cervical and anal cancer screening tests (e.g., Papanicolaou (Pap) test, HPV DNA tests), there is a lack of screening tools for other types of HPV-related cancers [ 7 ]. However, HPV vaccination rates in the U.S. remain suboptimal, attributed to missed opportunities for vaccination (i.e., health visits during which at least one vaccine, other than the HPV vaccine, is received) [ 21 , 22 , 23 ]. The Centers for Disease Control and Prevention (CDC) estimated that if the HPV vaccine was administered to all adolescent girls born in the year 2000 during health visits when they received another vaccine, HPV vaccine initiation by age 13 years could have reached 91.3% [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Vaccination is imperative for preventing HPV-related disease because, aside from cervical and anal cancer screening tests (e.g., Papanicolaou (Pap) test, HPV DNA tests), there is a lack of screening tools for other types of HPV-related cancers [ 7 ]. However, HPV vaccination rates in the U.S. remain suboptimal, attributed to missed opportunities for vaccination (i.e., health visits during which at least one vaccine, other than the HPV vaccine, is received) [ 21 , 22 , 23 ]. The Centers for Disease Control and Prevention (CDC) estimated that if the HPV vaccine was administered to all adolescent girls born in the year 2000 during health visits when they received another vaccine, HPV vaccine initiation by age 13 years could have reached 91.3% [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current HPV vaccines available to the general population have been shown to be safe and effective for cancer survivors [ 27 ], and the CDC and Children’s Oncology Group (COG) recommend vaccinating patients within 6 months after cancer treatment [ 25 ]. Despite this, HPV vaccination rates among young cancer survivors remain low; compared to the general population, HPV vaccination rates are as much as 20% lower for PYAC survivors and are well below the 80% Healthy People 2030 target [ 23 , 30 , 31 , 32 , 33 ]. A recent review of five cancer centers reported that only 24% of cancer survivors have initiated HPV vaccination, with just 13.5% completing the vaccine series [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 12 A western New York retrospective review of 312 patients diagnosed with cancer at under 10 y old found that only 43.5% (27/62) males and 55.1% (43/78) of females had completed the three-dose vaccine series. 13 …”
Section: Introductionmentioning
confidence: 99%